Current status and risk determinants of locomotive syndrome in geriatric cancer survivors in China-a single-center cross-sectional survey - Yu-Ling Yang; Hui Su; Hui Lu; Hui Yu; Jing Wang; Yu-Qing Zhou; Ling Li; Ying Chen (Frontiers Media S.A., 2024)
ObjectiveTo assess the prevalence and risk determinants of locomotive syndrome (LS) in geriatric cancer survivors in China. To generate evidence-based insights for the clinical prevention and intervention strategies concerning LS in this vulnerable population, emphasizing the need for integrated public health initiatives focused on maintaining mobility among geriatric cancer survivors.MethodsSix hundred geriatric cancer survivors were recruited at a hospital in China. A demographic questionnaire, the International Physical Activity Questionnaire-Short (IPAQ-S), and the Geriatric Locomotive Function Scale (GLFS-25) were administered. Survivors were stratified into three physical activity level (PAL) groups via IPAQ-S scores: low, medium, and high. LS was operationally defined via GLFS-25 scores, with cut-offs established for LS-1, LS-2, and LS-3. Elevated GLFS-25 scores signified deteriorated motor function (MF) and increased severity of LS. Data analysis was done to investigate the risk determinants to the occurrence and exacerbation of LS among geriatric cancer survivors.ResultsOf the 524 geriatric cancer survivors who completed the study, 292 (55.7%) were diagnosed with LS, including 152 (29%) categorized under LS-1, 52 (9.9%) under LS-2, and 88 (16.8%) under LS-3. Univariate analysis indicated that variations in exercise habits, prior occupational type, presence of tumor metastasis or recurrence, visual impairments, somatosensory abnormalities, and PAL were significantly associated with differing occurrences and severities of LS (p < 0.05). Ordinal logistic regression revealed that prior occupational type (OR = 0.466), tumor metastasis (OR = 0.404), tumor recurrence (OR = 0.341), and PAL (medium: OR = 7.178; high: OR = 1.984) were independent risk determinants modulating both the occurrence and severity of LS in cancer survivors (p < 0.05).ConclusionThe occurrence of LS is notably elevated among geriatric cancer survivors in China, indicating a significant public health concern. Individuals who were previously engaged in non-physically demanding occupations and those with histories of tumor metastasis or recurrence, coupled with reduced PAL, demonstrate a heightened susceptibility and severities to LS. Early identification of these risk determinants is imperative for mitigating the onset and progression of LS. Comprehensive public health strategies, including regular screening programs, targeted physical rehabilitation initiatives, and community-based interventions, are essential to mitigate the onset and progression of LS in this vulnerable population, ultimately reducing its broader impact on aging-related health outcomes.